Concurrent Library Correctness on the TSO Memory Model - Burckhardt, Sebastian; Gotsman, Alexey; Musuvathi, Madanlal; Yang, Hongseok; Musuvathi, Madan (21st European Symposium on Programming (ESOP 2012), 2012)
Linearizability is a commonly accepted notion of correctness for libraries of concurrent algorithms. Unfortunately, it is only appropriate for sequentially consistent memory models, while the hardware and software platforms that algorithms run on provide weaker consistency guarantees. In this paper, we present the first definition of linearizability on a weak memory model, Total Store Order (TSO), implemented by x86 processors. We establish that our definition is a correct one in the following sense: while proving a property of a client of a concurrent library, we can soundly replace the library by its abstract implementation related to the original one by our generalisation of linearizability. This allows abstracting from the details of the library implementation while reasoning about the client. We have developed a tool for systematically testing concurrent libraries against our definition and applied it to several challenging algorithms.